The Bogleheads' guide to the three-fund portfolio : how a simple portfolio of three total market index funds outperforms most investors with less risk - Larimore, Taylor, 1924- (John Wiley & Sons, Inc., 2018)
Twenty benefits from the three-fund total market index portfolio. The Bogleheads' Guide to The Three-Fund Portfolio describes the most popular portfolio on the Bogleheads forum. This all-indexed portfolio contains over 15,000 worldwide securities, in just three easily-managed funds, that has outperformed the vast majority of both professional and amateur investors. If you are a new investor, or an experienced investor who wants to simplify and improve your portfolio, The Bogleheads' Guide to The Three-Fund Portfolio is a short, easy-to-read guide to show you how.